Research on a New Type of Energy Feedback Cascade Multilevel Inverter System - Wang Pan; Liu Fei; Zha Xiaoming; Yu Jianhua; Wang Xiangbing (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Traditional cascade multilevel inverter can only transmit one-direction of energy. This paper proposes a new cascade multilevel inverter topology and control strategy based on part units to realize the energy feedback. By using PWM converter to replace uncontrollable converter in part units of the traditional inverter, and combining the inverter with H-bridge inverter, the two-direction running of the cascade inverter is realized. A double closed loop control strategy is used to obtain fine control characteristic of input current. The carrier phase-shifted SPWM technology is adopted in the cascade inverter to reduce harmonious wave of output voltage and current, meanwhile, a new type of bypass control method is proposed to collect all the feedback energy and restore it into the energy feedback units. According to the simulation of a three-phase and five-unit cascaded inverter with three energy feedback units, the results demonstrate that the proposed inverter can be input near sinusoidal current , and realize two-way flow of energy automatically with simplified phase shifting transformer structure, and show its feasibility and effectiveness. DOI: http://dx.doi.org/10.11591/telkomnika.v11i1.1864